Batter Power-Up! - Jake Maddox (Stone Arch Books, 2024)
Zack Jones is a whiz when it comes to playing defense in the outfield. But when it comes to hitting a baseball, his batting skills come up short. Luckily, his friend Jamie has an incredible virtual reality system that helps him train to improve his batting game. But when the VR system goes up in smoke, Zack loses his confidence and isn't sure he can perform at the plate when his team needs him. Will Zack find faith in himself and keep his bat powered up when the game is on the line?
Keywords: Sports Stories -- Sports Stories